75.9k views
2 votes
What’s the correct answer for this?

What’s the correct answer for this?-example-1
User Sakeer
by
4.8k points

2 Answers

5 votes

Answer:

A

Explanation:

  • Rule => (a+b)²=a² + 2ab + b²
  • Rule => (a-b)² = a² -2ab + b²

x² - 6x - 33 = 0

x² => a²

-6x => -2ab

Therefore, b=3

9 - ..... = -33

...... = 42

x² - 6x + 9 - 42 = 0

(x -3)² - 42 = 0

(x-3)² = 42

First option is answer

Hope this helps ^-^

3 votes

Answer:

The second one I believe!

User Dawsy
by
5.1k points